Analysing the Influence of Cultural Distance and Language Barriers on Academic Performance among International Students in Higher Education Institutions - Muthuswamy, Vimala Venugopal; G, Varshika (Journal of International Students, 2023)
This study investigates the intricate dynamics faced by international students in higher education institutions in Saudi Arabia, specifically examining the consequential impacts of cultural and language barriers on academic performance. Cultural distance, language barriers, and social adjustment are analysed for their influence on academic outcomes, with a focus on understanding the mediating role of self-efficacy and the moderating impact of cultural intelligence. Methodologically, data from 220 students were meticulously collected through surveys, and quantitative analysis using SPSS was employed. The results indicate that language barriers significantly affect academic performance, while social adjustment and cultural distance show insignificant effects on academic outcomes.